Genetically-Driven Enhancement of Dopaminergic Transmission Affects Moral Acceptability in Females but Not in Males: A Pilot Study - Pellegrini, Silvia; Palumbo, Sara; Iofrida, Caterina; Melissari, Erika; Rota, Giuseppina; Mariotti, Veronica; Anastasio, Teresa; Manfrinati, Andrea; Rumiati, Rino; Lotto, Lorella; Sarlo, Michela; Pietrini, Pietro (Frontiers in Behavioral Neuroscience, 2017)
Moral behavior has been a key topic of debate for philosophy and psychology for a long time. In recent years, thanks to the development of novel methodologies in cognitive sciences, the question of how we make moral choices has expanded to the study of neurobiological correlates that subtend the mental processes involved in moral behavior. For instance, in vivo brain imaging studies have shown that distinct patterns of brain neural activity, associated with emotional response and cognitive processes, are involved in moral judgment. Moreover, while it is well-known that responses to the same moral dilemmas differ across individuals, to what extent this variability may be rooted in genetics remains yet to be understood. Because dopamine is a key modulator of neural processes underlying executive functions, we questioned whether genetic polymorphisms associated to decision-making and to dopaminergic neurotransmission modulation would contribute to the observed variability in moral judgment. To this aim, we genotyped five genetic variants of the dopaminergic pathway (rs1800955 in the dopamine receptor D4 (DRD4) gene, DRD4 48bp variable number of tandem repeat (VNTR), solute carrier family 6 member 3 (SLC6A3) 40bp VNTR, rs4680 in the catechol-O-methyl transferase (COMT) gene and rs1800497 in the ankyrin repeat and kinase domain containing 1 (ANKK1) gene) in 200 subjects, who were requested to answer to 56 moral dilemmas. As these variants are all located in genes belonging to the dopaminergic pathway, they were combined in multilocus genetic profiles for the association analysis. While no individual variant showed any significant effect on moral dilemma responses, the multilocus genetic profile analysis revealed a significant gender specific influence on human moral acceptability. Specifically, those genotype combinations that improve dopaminergic signaling selectively increased moral acceptability in females, by making their responses to moral dilemmas more similar to those provided by males. As females usually give more emotionally-based answers and engage the 'emotional brain' more than males, our results, though preliminary and therefore in need of replication in independent samples, suggest that this increase in dopamine availability enhance the cognitive and reduce the emotional components of moral decision-making in females, thus favoring a more rationally-driven decision process.